Visual Structure and Verbal Narrative: Reproduction of Socio-Cultural Values and Political Realities in the 2nd Vice-Presidential Debate of the 2024 Presidential Election - Yuniar, Ririt; Titania, Fattiha A.; Febriana, Karina (Advances in Social Sciences Research Journal, 2025)
It appears that there has been a reproduction of values behind the stage of the 2024 Presidential & Vice-Presidential Candidate debate, the use of costumes is not just a cloth covering the body, but a symbol of identity and political communication strategy carried through the elaboration of social and cultural capital. This study aims to answer three things, namely: First, to see the socio-cultural values carried in the construction of the political reality of the 2024 presidential and vice-presidential election campaign in Indonesia for the Ganjar-Mahfud candidates in the 2nd Vice-Presidential Candidate debate through the visual structure of costumes in the context of verbal content narrative; Second, to find out the socio-political reality constructed in the interpretation of socio-cultural values reproduced in the candidate’s Performance, especially only in the subjective political reality section; Third, to find out the meaning of the interpretation of the candidate’s Performance displayed. Values, norms, symbols of religion, ethnicity, locality or institutions for the candidate’s legitimacy in his victory are the focus of discussion and analysis. The urgency of being studied and researched in academic literature to answer why, in the context of the reproduction of socio-cultural values and political reality, it is necessary to look at the context of social class based on social and cultural capital, so that it produces a specific meaning in the candidate’s Performance? This study uses the socio-cultural reproduction theory and the political reality concept. An interpretive qualitative method to examine the reproduction of socio-cultural values and political reality through the visual structure of costumes, then contextualized with tabulated verbal narrative content to analyze the candidate’s performance according to the themes and sub-themes, the substance of the content given by the committee to Vice-Presidential Candidate Mahfud MD. The research findings show three things, namely: First, a comprehensive understanding of the reproduction of socio-cultural values through the display of the visual structure of costumes and verbal narrative content in the dialogue of the 2nd debate of the 2024 Vice-Presidential Candidate; Second, the construction of the political reality of the candidates carried through the YouTube channels of the Indonesian General Elections Commission (KPU RI) and SCTV; Third, Interpretation of Candidates’ Performance in the Featured Reality by the candidates. The study results indicate a reproduction of socio-cultural values and political reality that produces the performance of the Ganjar-Mahfud candidates based on subjective political reality.